Pengabdian Masyarakat: Solusi Penyedot Asap Blower Otomatis untuk Lombok Center IT - akbar, taufik; Komala Dewi P, Intan (Jurnal Teknologi Informasi untuk Masyarakat, 2023)
Solder is a heating tool used to melt tenol so that it can be used to connect the component legs to the PCB (printed circuit board). The smoke that arises when soldering contains lead (Pb), this is because tenol solder is a mixture of 63% tin and 36% lead. Lead (Pb) is a heavy metal that is very dangerous for the human body. Lead exhibits toxic properties to the nervous system, hemetologic, hemetotoxic and affects kidney function. For this reason, we need a tool that is able to suck in the smoke resulting from the soldering process and filter it so that it is not harmful to the body. The process of making a prototype of this tool goes through four stages, namely literature study, tool design, tool making and tool realization. The design of the prototype of this tool is divided into making exhaust chimneys, sensors and controllers. The sensor part of this tool uses MQ-2. The sensor readings will be processed by the Arduino Uno microcontroller which then sends the message to the relay, then the relay will turn on the PC fan to suck up the solder fumes that arise.